Successful Embolization in Recurrent Hemoptysis Caused by Pulmonary Aspergilloma: A Case Report: Successful Embolization in Recurrent Hemoptysis Caused by Pulmonary Aspergilloma - Yaman, Muli; Sugiri, Jane; Putra, Ngakan; Santosaningsih, Dewi; Aslam, Achmad (Universitaas Brawijaya, 2023)
Background: Aspergilloma is a fungal infection that can cause recurrent hemoptysis. One of the treatment modalities is embolization, which has a success rate of 85% to 100%, although the recurrence rate may reach 10% to 33%. Case Illustration: A 29-year-old female came to the emergency ward with recurrent hemoptysis. She had a history of tuberculosis with completed treatment 7 years ago. Chest radiography showed left lung tuberculosis with emphysematous lung. Chest CT with contrast revealed an air-crescent sign, and culture from bronchoalveolar lavage (BAL) showed Aspergillus spp. Then, she was diagnosed with pulmonary aspergilloma. Embolization was performed in the left internal mammary artery, and the blushing was decreased by 80%. However, the hemoptysis was still recurrent; a second embolization was performed in the left supreme intercostal artery, costocervical trunk artery, and bronchial artery, resulting in no blushing. The patient had no further episodes of hemoptysis, and her antifungal therapy was changed from fluconazole to voriconazole. Discussion: Recurrent hemoptysis can be caused by pulmonary aspergilloma. Embolization is usually done to reduce bleeding before surgery. The patient had performed embolization 2 times with no further episodes of hemoptysis. Surgical resection as a definitive treatment was recommended in this case, but the patient refused. Therefore, the patient’s management was optimized using voriconazole and embolization for the hemoptysis. Conclusion: Management of recurrent hemoptysis in patients with aspergilloma may include embolization and antifungal treatment which give improved clinical outcomes. Keywords: recurrent hemoptysis, embolization, aspergilloma, tuberculosis